Taxonomic notes on the Cephalaria sect. Atrocephalae (Caprifoliaceae) from Iran - Ranjbar, Massoud; Ranjbar, Zahra (Phytotaxa, 2015)
Cephalaria bojnordensis (Caprifoliaceae) is described and illustrated as a new species from Khorasan Province, north-east Iran. The characters that distinguish this new species from C. microcephala and C. isurica are provided along with a key to the Iranian species in Cephalaria sect. Atrocephalae. In addition, a lectotype is designated for C. microcephala.